Pemanfaatan Jerami Kedelai pada Pakan Induk Sapi Silangan Simmental-Peranakan Ongole - Batseba M.W. Tiro; Petrus A. Beding (Politeknik Negeri Jember, 2018)
The onset of first postpartum estrous is an indicator in the beef cattle reproduction efficiency. Soybean straw is a local feed ingredients that contain phytoestrogen compounds. The present experiment was conducted to determine the effect of the use of soybean straw as a source of phytoestrogen to accelerate the onset of the first postpartum estrous of Simmental â€“ Ongole crossbred cows. This research applies by completely randomized design (CRD) consisted three treatments and each treatment is repeated five times. Treatment consist of : P0: control (standar feed), P1: control + 5 g of phytoestrogen (1.8 kg of soybean straw), and P2: control + 10 of g phytoestrogen (3.6 kg of soybean straw). The result showed that the use of soybean straw as a source of phytoestrogen increase consumption CP (P<0,05), whereas DM and TDN comsumption increased only slighthy (P>0,05). Supplementation of soybean straw as a source phytoestrogen are also likely to accelerate the first postpartum estrous. Â